Preparation method of filter element material for enhancing tobacco smoke adsorption
By constructing a metal organic frame and carbon skeleton on the filter element material and opening a breath flow channel on the carbon fiber felt, the existing filter element material has solved the problems of low efficiency, small capacity and large gas resistance to absorb tobacco smoke, achieving efficient adsorption and low gas resistance.
Patent Information
- Application Number
- CN202411652763.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-14
AI Technical Summary
The existing filter element materials are inefficient, have small capacity and large air resistance when absorbing tobacco smoke, and cannot effectively remove tobacco smoke from the air.
By constructing a metal organic frame containing carbonate particles on the filter element material, and coordinating with copper ions and zinc ions with benzene ring-containing pyrrolidine and bisamino-containing pyridine biligands, a porous adsorption material and a carbon framework are formed, and a gas flow channel from wide to narrow along the airflow direction is opened on the carbon fiber felt.
The specific surface area, pore capacity and tobacco smoke adsorption active sites of the filter element material are significantly improved, the adsorption efficiency and adsorption capacity are enhanced, and the gas resistance is reduced.
Smart Images

Figure CN119606059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air purification, and in particular to a method for preparing a filter element material for enhancing tobacco smoke adsorption. Background Art
[0002] Tobacco smoke includes second-hand smoke and third-hand smoke. Its main components are nicotine and its derivatives, benzene substances, aldehydes, particulate matter, tar and other components. Long-term exposure to it will have serious adverse effects on the normal life activities of the human body.
[0003] At present, porous materials such as activated carbon and molecular sieves are commonly used to treat tobacco smoke. However, the types, structures, and properties of compounds contained in tobacco smoke vary greatly. Commonly used activated carbon adsorption materials are limited by raw materials and process methods, and have problems such as low adsorption efficiency, small adsorption capacity, and large air resistance. They are not suitable for removing tobacco smoke from the air. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a filter element material for enhancing tobacco smoke adsorption, so as to solve the problems of low tobacco smoke adsorption efficiency, small capacity and large air resistance of the filter element material.
[0005] To achieve the above object, the present invention provides the following technical solutions: The present invention discloses a method for preparing a filter element material for enhancing tobacco smoke adsorption, which specifically comprises the following steps: Step S1: 50-100 parts by mass of filter element material, 8-16 parts by mass of ligand No. 1, 5-10 parts by mass of ligand No. 2, 3-6 parts by mass of o-phthalaldehyde, and 500-1000 parts by mass of solvent are evenly dispersed, and then 5-10 parts by mass of zinc salt and 10-15 parts by mass of copper salt are added, dispersed, and carbon dioxide gas is introduced, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, centrifugation is performed, the supernatant is discarded, and the obtained precipitate is freeze-dried, and finally high-temperature calcination is performed to obtain a functional material; Step S2: Dispersing the functional material, polyvinyl pyrrolidone and water uniformly to obtain a mixed solution; Step S3: immersing two pieces of carbon fiber felt containing airflow channels in the mixed solution, taking them out and combining the two pieces of carbon fiber felt into a whole with airflow channels inside, and freeze-drying them to obtain a filter element material with enhanced tobacco smoke adsorption.
[0006] Preferably, in step S1, the filter element material is one of carbon aerogel, silica aerogel, activated carbon, and graphene aerogel; the solvent is a mixed solution of ethanol, ether, and water in a volume ratio of 2:2:1; the zinc salt is one of zinc chloride, zinc sulfate, and zinc nitrate; and the copper salt is one of copper chloride, copper sulfate, and copper nitrate.
[0007] Preferably, in step S1, ligand No. 1 is one of 2-phenylpyrrolidine, 3-phenylpyrrolidine, 2-phenylethylpyrrolidine, and 2-(naphthalene-2-yl)pyrrolidine; ligand No. 2 is one of 2,3-diaminopyridine, 2,4-diaminopyridine, 2,5-diaminopyridine, and 3,4-diaminopyridine.
[0008] Preferably, in step S1, the carbon dioxide gas is introduced at a rate of 5 to 10 parts by mass / min for a time of 15 to 30 min.
[0009] Preferably, in step S1, the hydrothermal reaction temperature is 150-200° C., and the time is 5-10 h; the high-temperature calcination temperature is 900-1200° C., and the insulation time is 2-3 h.
[0010] Preferably, in step S2, the mass ratio of the functional material, polyvinyl pyrrolidone and water is (3-5): (0.5-1):100.
[0011] Preferably, in step S3, the airflow channel is a groove that is narrowed from wide to narrow along the airflow direction.
[0012] Preferably, in step S3, the immersion temperature is 60-80° C. and the time is 5-10 min.
[0013] Preferably, the volume density of the carbon fiber felt in step S3 is 0.2-0.7 g / cm 3 .
[0014] Preferably, the freeze-drying temperature in step S1 and step S3 is -40 to -60°C and the time is 10 to 24 hours.
[0015] Beneficial effects of the present invention: 1. By constructing a metal organic framework containing carbonate particles on the filter material, a porous adsorption material is formed during the subsequent drying and heat treatment process, which can effectively increase the specific surface area, pore capacity and active sites for tobacco smoke adsorption of the filter material, thereby enhancing the adsorption efficiency and adsorption capacity of the filter material for tobacco smoke; 2. By opening an airflow channel from wide to narrow along the airflow direction on the carbon fiber felt, not only can the uniformity of airflow distribution inside the carbon fiber felt be improved, but also the cross-sectional area of gas passage can be effectively reduced, thereby reducing the gas resistance of the filter element material; 3. Pyrrolidine containing a benzene ring and pyridine containing a diamino group are used to react with copper ions and zinc ions to form a coordination reaction, and then fixed on the filter material. After heat treatment, the formed carbon skeleton has a strong adsorption effect on nicotine and its derivatives in tobacco smoke, thereby increasing the adsorption efficiency of the filter material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1The present invention provides a method for preparing a filter element material for enhancing tobacco smoke adsorption; Figure 2 Schematic diagram of the gas channel of the carbon fiber felt in Example 1; Figure 3 Scanning electron microscope image of the functional material prepared in Example 1; Figure 4 Tobacco smoke adsorption test chart of different filter materials. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0018] like Figure 1 As shown, a method for preparing a filter element material for enhancing tobacco smoke adsorption specifically comprises the following steps: Step S1: 50-100 parts by mass of filter element material, 8-16 parts by mass of ligand No. 1, 5-10 parts by mass of ligand No. 2, 3-6 parts by mass of o-phthalaldehyde, and 500-1000 parts by mass of solvent are evenly dispersed, and then 5-10 parts by mass of zinc salt and 10-15 parts by mass of copper salt are added, dispersed, and carbon dioxide gas is introduced, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, centrifugation is performed, the supernatant is discarded, and the obtained precipitate is freeze-dried, and finally high-temperature calcination is performed to obtain a functional material; the filter element material is one of carbon aerogel, silica aerogel, activated carbon, and graphene aerogel; the solvent is a mixed solution of ethanol, ether, and water in a volume ratio of 2:2:1; the zinc salt is one of zinc chloride, zinc sulfate, and zinc nitrate; the copper salt is one of copper chloride, copper sulfate, and copper nitrate. Ligand No. 1 is one of 2-phenylpyrrolidine, 3-phenylpyrrolidine, 2-phenylethylpyrrolidine, and 2-(naphthalene-2-yl)pyrrolidine; ligand No. 2 is one of 2,3-diaminopyridine, 2,4-diaminopyridine, 2,5-diaminopyridine, and 3,4-diaminopyridine; the carbon dioxide gas introduction rate is 5-10 parts by mass / min, and the time is 15-30 minutes; the hydrothermal reaction temperature is 150-200°C, and the time is 5-10 hours; the high-temperature calcination temperature is 900-1200°C, and the insulation time is 2-3 hours; the freeze-drying temperature is -40--60°C, and the time is 10-24 hours.
[0019] Step S2: Disperse the functional material, polyvinyl pyrrolidone and water in a mass ratio of (3-5): (0.5-1): 100 to obtain a mixed solution.
[0020] Step S3: immerse two pieces of carbon fiber felt containing airflow channels in the mixed solution at 60-80°C for 5-10 minutes, take out and combine the two pieces of carbon fiber felt into a whole containing airflow channels inside, freeze-dry at -40--60°C for 10-24 hours, and obtain a filter element material with enhanced tobacco smoke adsorption.
[0021] Example 1: Obtained by the following method 60 parts by mass of carbon aerogel, 10 parts by mass of 2-phenylpyrrolidine, 5 parts by mass of 2,3-diaminopyridine, 3 parts by mass of o-phthalaldehyde, and 600 parts by mass of solvent (composed of ethanol, ether, and water in a volume ratio of 2:2:1) were evenly dispersed, and then 6 parts by mass of zinc chloride and 12 parts by mass of cupric chloride were added and dispersed, and carbon dioxide gas was introduced at a rate of 6 parts by mass / min for 20 minutes, and then transferred to a reactor, and hydrothermally reacted at 180°C for 6 hours. After the reaction was completed, centrifugation was performed, and the supernatant was discarded. The resulting precipitate was freeze-dried at -40°C for 24 hours, and finally kept warm at 1000°C for 2.5 hours to obtain a functional material. The functional material, polyvinyl pyrrolidone, and water were evenly dispersed in a mass ratio of 5:0.5:100 to obtain a mixed solution; Figure 2 As shown, the carbon fiber felt is provided with grooves which are from wide to narrow along the airflow direction. Two pieces of carbon fiber felt containing airflow channels are immersed in the mixed liquid at 60°C for 6 minutes. After being taken out, the two pieces of carbon fiber felt are combined into a whole containing airflow channels inside, and freeze-dried at -40°C for 24 hours to obtain a filter element material with enhanced tobacco smoke adsorption. Figure 3 This is a scanning electron microscope image of the functional material. It can be seen that the carbon aerogel is loaded with carbonized particles of the complex and there are many pores distributed on the functional material.
[0022] Example 2: Obtained by the following method 50 parts by mass of silica aerogel, 14 parts by mass of 3-phenylpyrrolidine, 8 parts by mass of 2,4-diaminopyridine, 4 parts by mass of o-phthalaldehyde, and 500 parts by mass of a solvent (composed of ethanol, ether, and water in a volume ratio of 2:2:1) were evenly dispersed, and then 5 parts by mass of zinc sulfate and 10 parts by mass of copper sulfate were added and dispersed. Carbon dioxide gas was introduced at a rate of 5 parts by mass / min for 30 minutes, and then transferred to a reactor for hydrothermal reaction at 200°C for 5 hours. After the reaction was completed, the mixture was centrifuged and the supernatant was discarded. The resulting precipitate was freeze-dried at -50°C for 10 hours, and finally kept warm at 1100°C for 2.5 hours to obtain a functional material. Functional material, polyvinyl pyrrolidone and water are evenly dispersed in a mass ratio of 4:0.6:100 to obtain a mixed solution; two pieces of carbon fiber felt containing airflow channels are immersed in the mixed solution at 70°C for 5 minutes, and after taking out, the two pieces of carbon fiber felt are combined into a whole containing an airflow channel inside, and freeze-dried at -50°C for 10 hours to obtain a filter element material for enhanced tobacco smoke adsorption.
[0023] Example 3: Obtained by the following method 100 parts by mass of activated carbon, 8 parts by mass of 2-phenylethylpyrrolidine, 10 parts by mass of 2,5-diaminopyridine, 5 parts by mass of o-phthalaldehyde, and 1000 parts by mass of a solvent (composed of ethanol, ether, and water in a volume ratio of 2:2:1) were evenly dispersed, and then 9 parts by mass of zinc nitrate and 14 parts by mass of copper nitrate were added and dispersed, and carbon dioxide gas was introduced at a rate of 10 parts by mass / min for 25 minutes. The mixture was then transferred to a reactor and hydrothermally reacted at 150°C for 10 hours. After the reaction was completed, the mixture was centrifuged and the supernatant was discarded. The resulting precipitate was freeze-dried at -60°C for 20 hours, and finally kept warm at 900°C for 3 hours to obtain a functional material. Functional materials, polyvinyl pyrrolidone and water are evenly dispersed in a mass ratio of 3:0.7:100 to obtain a mixed solution; two pieces of carbon fiber felt containing airflow channels are immersed in the mixed solution at 80°C for 7 minutes, and after taking out, the two pieces of carbon fiber felt are combined into a whole containing an airflow channel inside, and freeze-dried at -60°C for 20 hours to obtain a filter element material for enhanced tobacco smoke adsorption.
[0024] Example 4: Obtained by the following method 70 parts by mass of graphene aerogel, 16 parts by mass of 2-(naphthalene-2-yl)pyrrolidine, 6 parts by mass of 3,4-diaminopyridine, 6 parts by mass of o-phthalaldehyde, and 700 parts by mass of solvent (composed of ethanol, ether, and water in a volume ratio of 2:2:1) were evenly dispersed, and then 10 parts by mass of zinc nitrate and 15 parts by mass of copper nitrate were added and dispersed, and carbon dioxide gas was introduced at a rate of 7 parts by mass / min for 10 minutes. Then, the mixture was transferred to a reactor and hydrothermally reacted at 160°C for 8 hours. After the reaction was completed, the mixture was centrifuged and the supernatant was discarded. The resulting precipitate was freeze-dried at -50°C for 15 hours, and finally kept warm at 1200°C for 2 hours to obtain a functional material. Functional material, polyvinyl pyrrolidone and water are evenly dispersed in a mass ratio of 5:1:100 to obtain a mixed solution; two pieces of carbon fiber felt containing airflow channels are immersed in the mixed solution at 75°C for 10 minutes, and after taking out, the two pieces of carbon fiber felt are combined into a whole containing an airflow channel inside, and freeze-dried at -50°C for 15 hours to obtain a filter element material for enhanced tobacco smoke adsorption.
[0025] Example 5: Obtained by the following method 80 parts by mass of carbon aerogel, 12 parts by mass of 2-phenylethylpyrrolidine, 7 parts by mass of 3,4-diaminopyridine, 5 parts by mass of o-phthalaldehyde, and 800 parts by mass of solvent (composed of ethanol, ether, and water in a volume ratio of 2:2:1) were evenly dispersed, and then 8 parts by mass of zinc nitrate and 13 parts by mass of copper nitrate were added and dispersed. Carbon dioxide gas was introduced at a rate of 8 parts by mass / min for 15 minutes, and then transferred to a reactor for hydrothermal reaction at 170°C for 7 hours. After the reaction was completed, the mixture was centrifuged and the supernatant was discarded. The resulting precipitate was freeze-dried at -60°C for 18 hours, and finally kept warm at 1000°C for 3 hours to obtain a functional material. Functional material, polyvinyl pyrrolidone and water are evenly dispersed in a mass ratio of 4:0.8:100 to obtain a mixed solution; two pieces of carbon fiber felt containing airflow channels are immersed in the mixed solution at 65°C for 8 minutes, and after taking out, the two pieces of carbon fiber felt are combined into a whole containing an airflow channel inside, and freeze-dried at -60°C for 18 hours to obtain a filter element material for enhanced tobacco smoke adsorption.
[0026] Comparative Example 1 The difference between this comparative example and Example 1 is that the carbon aerogel does not have step S1 and is directly added to step S2 for subsequent operations.
[0027] Comparative Example 2 The difference between this comparative example and Example 1 is that step S2 and step S3 are not performed, and the functional material prepared in step S1 is directly used.
[0028] Comparative Example 3 The difference between this comparative example and Example 1 is that the carbon fiber felt used in step S3 does not have a gas channel.
[0029] Comparative Example 4 This comparative example uses commercial activated carbon as a blank control.
[0030] Referring to the test method for wood activated carbon in GB / T 12496-1999, tobacco smoke adsorption experiments were conducted on the materials of Examples 1-5 and Comparative Examples 1-4 under the same test conditions to test the time to reach equilibrium and the adsorption amount of nicotine adsorption.
[0031] Depend on Figure 4It can be seen that Example 1 has greater adsorption efficiency and adsorption capacity than Comparative Example 1, Comparative Example 2, and Comparative Example 4. This is mainly because a metal organic framework containing carbonate particles is constructed on the filter element material to form a porous adsorption material during the subsequent drying and heat treatment processes, which can effectively improve the specific surface area, pore capacity and tobacco smoke adsorption active sites of the filter element material, thereby enhancing the adsorption efficiency and adsorption capacity of the filter element material for tobacco smoke; at the same time, a pyrrolidine containing a benzene ring and a pyridine containing a diamino group are used to coordinate with copper ions and zinc ions, and the benzene ring can be combined with the filter element material through intermolecular forces and then fixed on the filter element material. After heat treatment, the carbon skeleton formed by the pyrrolidine group and the pyridine group is similar to the carbon skeleton structure of the nicotine molecule, and can produce a strong adsorption effect on nicotine and its derivatives in tobacco smoke, thereby increasing the adsorption efficiency of the filter element material. In addition, compared with Comparative Example 3, Example 1 can not only improve the uniformity of airflow distribution inside the carbon fiber felt, but also effectively reduce the cross-sectional area through which gas passes, thereby reducing the gas resistance of the filter element material, by opening an airflow channel from wide to narrow along the airflow direction on the carbon fiber felt.
[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a filter element material for enhancing tobacco smoke adsorption, characterized in that: The specific steps include: Step S1: 50-100 parts by mass of filter element material, 8-16 parts by mass of ligand No. 1, 5-10 parts by mass of ligand No. 2, 3-6 parts by mass of o-phthalaldehyde, and 500-1000 parts by mass of solvent are evenly dispersed, and then 5-10 parts by mass of zinc salt and 10-15 parts by mass of copper salt are added, dispersed, and carbon dioxide gas is introduced, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, centrifugation is performed, the supernatant is discarded, and the obtained precipitate is freeze-dried, and finally high-temperature calcination is performed to obtain a functional material; Step S2: Dispersing the functional material, polyvinyl pyrrolidone and water uniformly to obtain a mixed solution; Step S3: immersing two pieces of carbon fiber felt containing airflow channels in the mixed solution, taking them out and combining the two pieces of carbon fiber felt into a whole with airflow channels inside, and freeze-drying them to obtain a filter element material with enhanced tobacco smoke adsorption.
2. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S1, the filter element material is one of carbon aerogel, silica aerogel, activated carbon, and graphene aerogel; the solvent is a mixed solution of ethanol, ether, and water in a volume ratio of 2:2:1; the zinc salt is one of zinc chloride, zinc sulfate, and zinc nitrate; and the copper salt is one of copper chloride, copper sulfate, and copper nitrate.
3. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S1, ligand No. 1 is one of 2-phenylpyrrolidine, 3-phenylpyrrolidine, 2-phenylethylpyrrolidine, and 2-(naphthalene-2-yl)pyrrolidine; ligand No. 2 is one of 2,3-diaminopyridine, 2,4-diaminopyridine, 2,5-diaminopyridine, and 3,4-diaminopyridine.
4. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S1, the carbon dioxide gas is introduced at a rate of 5 to 10 parts by mass / min for a time of 15 to 30 min.
5. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S1, the hydrothermal reaction temperature is 150-200° C., and the time is 5-10 hours; the high-temperature calcination temperature is 900-1200° C., and the insulation time is 2-3 hours.
6. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S2, the mass ratio of the functional material, polyvinyl pyrrolidone and water is (3-5):(0.5-1):
100.
7. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S3, the airflow channel is a groove that is gradually narrowed along the airflow direction.
8. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: In step S3, the immersion temperature is 60-80° C. and the immersion time is 5-10 min.
9. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: The volume density of the carbon fiber felt in step S3 is 0.2-0.7 g / cm 3 .
10. The method for preparing a filter element material for enhancing tobacco smoke adsorption according to claim 1, characterized in that: The freeze-drying temperature in step S1 and step S3 is -40 to -60°C and the time is 10 to 24 hours.